2021
DOI: 10.3389/fmolb.2020.599142
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumor Mutation Burden and Immune Infiltrates in Hepatocellular Carcinoma Based on Multi-Omics Analysis

Abstract: We aimed to explore the tumor mutational burden (TMB) and immune infiltration in HCC and investigate new biomarkers for immunotherapy. Transcriptome and gene mutation data were downloaded from the GDC portal, including 374 HCC samples and 50 matched normal samples. Furthermore, we divided the samples into high and low TMB groups, and analyzed the differential genes between them with GO, KEGG, and GSEA. Cibersort was used to assess the immune cell infiltration in the samples. Finally, univariate and multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Unfortunately, however, few clinical studies have revealed the role of TMB in HCC. We and others found a significant correlation between TMB and immune infiltration in HCC (5)(6)(7). Most importantly, the PS model was significantly associated with TMB and immune infiltration.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Unfortunately, however, few clinical studies have revealed the role of TMB in HCC. We and others found a significant correlation between TMB and immune infiltration in HCC (5)(6)(7). Most importantly, the PS model was significantly associated with TMB and immune infiltration.…”
Section: Discussionsupporting
confidence: 56%
“…Most importantly, TMB status was significantly associated with PS, and in other words, patients in the high-score group may have also had a high level of TMB (Figures 4B, C). In addition, the 3 most frequently mutated genes in HCC were employed as stratification factors, and therefore, the correlation between PS and OS was further investigated in the TCGA cohort 6 . The data showed that in the cohort of patients with wild-type or mutant TP53, wild-type or mutant TTN, and wild-type or mutant CTNNB1, PS still possessed clinically and statistically significant value for predicting patient prognosis (Figures 4D-I).…”
Section: The Ps Was Associated With Tmbmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue-agnostic biomarkers such as tumour mutation burden (TMB) and MSI have been examined for cancer immunotherapy 57 - 59 . TMB has been utilised as a predictive biomarker in cancer immunotherapy in several studies 11 , 60 - 62 . Our previous study demonstrated significant association of TMB with poor clinical outcomes in HCC patients 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The terpenoid and triterpenoid compounds are the strongest inhibitor [ 2 , 3 ]. Previous studies reported that rutin had the best inhibitory effect, even compared to the FDA-approved COVID19 antiviral (Remdesivir) [ 2 , 5 ]. This terpenoid is known to bind stably to the SARS-CoV-2 main protease receptor (PDB ID 6YNQ).…”
Section: Introductionmentioning
confidence: 99%